Pengaruh Transformational Leadership, Iklim Organisasi, Stres Kerja, Terhadap Kompetensi Motivasi Kerja dan Kinerja Guru SMP Negeri Di Provinsi Sulawesi Barat - Hasanuddin Lauda; I A Brahmasari; Amiartuti Kusmaningtyas (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2018)
The aim of this study was to analyze the effect of work stress, motivation, and competence of teachers, the performance of teachers in the province of West Sulawesi.The population in this study was the teacher of junior high school has been accredited by the Ministry of Education, with the criteria professorship at least 5 years, Minimum educational backgrounds S-1 and certified. They are a total of 269 junior high school teachers in four districts in West Sulawesi province, while samples taken by Slovin formula and the result was 161 respondents. This study used a questionnaire as the main instrument. And a questionnaire in the form of a modified Likert scale with response options from Agree to Strongly Agree. The data collected is processed by SEM (Structural Equation Modelling) technique with AMOS program version 19.These results indicate that the motivation and competence of junior high school teachers in West Sulawesi get high rankings in the category, and people could improve their performance. While the hypothesis testing results prove that: (1) Work stress a significant effect on the competence of teachers; (2) work motivation significant effect on the competence of teachers; (3) Stress significant effect on teacher performance; (4) Motivation significant effect on teacher performance; and (5) Competence of teachers significantly influence the performance of teachers. Thus, it means that the results of this study prove that all of this hypothesis is accepted.